2023
DOI: 10.1002/jmri.28977
|View full text |Cite
|
Sign up to set email alerts
|

Noninvasive Magnetic Resonance Imaging Measures of Glymphatic System Activity

Koji Kamagata,
Yuya Saito,
Christina Andica
et al.

Abstract: The comprehension of the glymphatic system, a postulated mechanism responsible for the removal of interstitial solutes within the central nervous system (CNS), has witnessed substantial progress recently. While direct measurement techniques involving fluorescence and contrast agent tracers have demonstrated success in animal studies, their application in humans is invasive and presents challenges. Hence, exploring alternative noninvasive approaches that enable glymphatic research in humans is imperative. This … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 98 publications
0
3
0
Order By: Relevance
“…Second, the study did not employ MRI-based tracers, considered the current gold standard for assessing glymphatic function in humans. 17 However, the ALPS index showed a high correlation with glymphatic clearance function, as determined through glymphatic MRI following intrathecal administration of gadolinium. 14 Third, it is important to note that the ALPS index does not solely assess the diffusivity of the perivenous space surrounding the deep medullary vein; it is also influenced by the adjacent white matter microstructure within the ROI.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Second, the study did not employ MRI-based tracers, considered the current gold standard for assessing glymphatic function in humans. 17 However, the ALPS index showed a high correlation with glymphatic clearance function, as determined through glymphatic MRI following intrathecal administration of gadolinium. 14 Third, it is important to note that the ALPS index does not solely assess the diffusivity of the perivenous space surrounding the deep medullary vein; it is also influenced by the adjacent white matter microstructure within the ROI.…”
Section: Discussionmentioning
confidence: 93%
“…A more recent approach, diffusion tensor imaging along the perivascular space (DTI-ALPS), based on diffusion MRI, has emerged as a promising noninvasive method for studying the human glymphatic system. 17,18 The DTI-ALPS method yields the ALPS index, representing the ratio of diffusivity along the perivascular space surrounding the deep medullary vein at the lateral ventricle body level to diffusivity in a direction perpendicular to the major fiber tracts. 17,18 At the level of the lateral ventricle body, the medullary veins run perpendicular to the ventricular wall, paralleling the direction of the perivascular space, whereas the medullary arteries and veins, as vessels of the brain parenchyma, accompany the perivascular space, which is a principal drainage pathway of the glymphatic system.…”
Section: Introductionmentioning
confidence: 99%
“…DTI along the PVS (DTI-ALPS) around deep medullary veins is an emerging noninvasive technique for evaluating the glymphatic system in humans. The ALPS index represents the CSF efflux function along the perivenous spaces, although additional validation studies are needed ( 138 ). Three recent studies performed in population-based cohorts or in patients with sporadic cSVD showed that the DTI-ALPS index was negatively related to the presence and severity of cSVD MRI markers (WMH, lacunes, microbleeds, visible PVS in the basal ganglia, and brain atrophy), suggestive of a declined glymphatic function ( 139 141 ).…”
Section: Regulation Of Fluids In the Brainmentioning
confidence: 99%